Psychological contract breach and mental health: The role of equity sensitivity and self-control - Justice Mensah; Kwesi Amponsah-Tawiah; Nana Kojo Ayimadu Baafi (Organization Management Journal (OMJ), 2024)
Purpose - This study aims to extend the literature on psychological contracts, employee mental health, selfcontrol and equity sensitivity among employees in Ghana. Design/methodology/approach - Data for this study came from a sample of 484 employees from an organisation in the telecommunication sector of Ghana. The details of the study were discussed with employees after which they were given the choice to participate in the study. Findings - The present study found that psychological contract breach is directly associated with mental health and indirectly related to mental health through equity sensitivity and self-control. Originality/value - The findings suggest that psychological contracts are important aspects of the employment relationship that could be used to enhance employee mental health. Furthermore, enhancing employees' self-control and resolving issues of individuals high on equity sensitivity are effective ways that organisations can deploy to sustain mental health in the face of psychological contract breaches.
Keywords: 650; Mental health; Psychological contract; Self-control; Equity sensitivity; Psychological contract breach